Serological Investigation of Akabane Virus Infection in Cattle and Sheep in Nigeria - Daniel Oladimeji Oluwayelu; Comfort Oluladun Aiki-Raji; Emmanuel Chibuzor Umeh; Samat Odunayo Mustapha; Adebowale Idris Adebiyi (Advances in Virology)
Akabane virus (AKAV) is recognized as an important pathogen that causes abortions and congenital malformations in ruminants. However, it has not received adequate attention in Nigeria. Therefore, in investigating this disease, serum samples from 184 (abattoir and farm) head of cattle and 184 intensively reared sheep from two states in southwest Nigeria were screened for antibodies against AKAV using enzyme-linked immunosorbent assay. An overall seropositivity of 70.1% (129/184) was obtained with antibodies being detectable in 73.8% of abattoir (trade) cattle and 40.0% in farm cattle, while 4.3% (8/184) seropositivity was observed in sheep. All the age groups of cattle tested had seropositive animals, 0-1 year (1/7, 14.3%), 2-3 years (17/34, 50.0%), 4-5 years (92/121, 76.0%), and >5 years (19/22, 86.4%), while in sheep only the age groups of 2-3 and 4-5 years showed seropositivity of 4.1% (4/97) and 8.2% (4/49), respectively. The detection of antibody-positive animals among unvaccinated cattle and sheep provides evidence of AKAV infection in Nigeria. These findings call for continuous monitoring of the disease among ruminants in order to ascertain the actual burden and increase awareness of the disease. This will facilitate early detection and aid the development of appropriate control measures against the disease in Nigeria.